Development of PBL-Based E-Modules on Work and Energy Materials Integrated with Nutrition to Improve Cognitive Learning Outcomes of Class X Students - Mulyanengsih, Ratu; Juita Nurhidayah, Isna; Dzakiruddin, Muhammad; Crosita Octaria, Yessi (Perspektif Ilmu Pendidikan, 2023)
Abstract, Almost one third of Indonesian adolescents aged 15-18 years old are stunted, while many also have overweight and obesity problem. Nutrition education can be done by integrating nutritional information and concepts into certain subjects, one of which is physics. Subject in physics which in line with the concept of nutrition are work and energy. In work and energy subject, it discusses the concept of the relationship between work, energy, the law of conservation of energy, the concept has strong relationship with nutrition which is a source of energy needed to do work. This research is a development research with the ADDIE model, which has 5 stages, Analyze; (2) Design; (3) Develop; (4) Implement; and (5) Evaluate [19]. The purpose of this study is "Produce feasible and effective PBL e-module learning media to improve learning outcomes and increase understanding of the importance of nutritional intake among adolescents", which can be accessed on smartphones. The e-module was tested on 36 grade X MIPA students at SMAN 30 Jakarta. The study was conducted from March to October 2022. The method used is a quasi-experimental method using a pretest-posttest control group design. The media is validated by media experts and material experts using instruments. Based on the calculation of validation of media experts and material experts on the PBL-based nutrition-integrated business and energy (E-MUEGIZ) E-module, it is included in the very valid category, meaning that the media is suitable for use. While Based on the value of N-Gain it can be said that the E-Module of effort and energy integrated nutrition (E-MUEGIZ) can increase understanding of the importance of nutrition as a source of energy. Keywords: Cognitive Learning; E-Module Development; Problem Based Learning; Effort and Energy, Nutrition